Entrepreneurial optimism and creative destruction - Lars Persson; Thomas Seiler (Research Institute of Industrial Economics (IFN), 2018)
We provide empirical evidence that uncertainty (rather than risk) and optimism are distinctive characteristics of high-impact entrepreneurial firms (recently listed firms) relative to old, incumbent firms. Based on this evidence, we construct an entrepreneurial entry predation model with uncertainty. We show that entrepreneurial optimism can mitigate problems associated with strong incumbents' attempts to protect markets using predatory threats. Entrepreneurial optimism can also create a strategic advantage for entrepreneurs since incumbents may react by being less aggressive in product market interactions, which will benefit not only the profitability of the entrepreneur's venture but also consumers via lower prices.
Keywords: L20; L26; M20; O30; 330; Uncertainty; Optimism; Entrepreneurial firms; Predation; Positive externalities; Automatic textual analysis